Coal-based benzenecarboxylic acid ester plasticizer, preparation method and application thereof
Patent Information
- Application Number
- CN202611018041.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-09
AI Technical Summary
建立“低阶煤解聚产物→环保增塑剂”的利用路径,解决现有石油基路线原料来源单一与煤基路线分离应用瓶颈大的双重产业难题
(1)原料来源创新:以储量丰富、成本低廉的褐煤为原料,替代了石油基芳烃原料,拓宽了增塑剂生产的原料来源。
Smart Images

Figure CN122563169B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material additives technology, specifically to a coal-based phenylcarboxylic acid ester plasticizer and its preparation method, as well as the application of the plasticizer in polyvinyl chloride. Background Technology
[0002] Plasticizers are key additives that improve the processing performance of polymer materials (especially polyvinyl chloride, PVC), enhancing their flexibility and ductility. They are widely used in plastics processing, cables, pipes, medical devices, food packaging, and many other fields. Currently, plasticizers are classified in various ways. Based on raw material source, they can be mainly divided into two categories: petroleum-based plasticizers and bio-based plasticizers. Petroleum-based plasticizers are synthesized from petrochemical products and constitute the majority of the current plasticizer market, accounting for over 80% of total plasticizer production. They mainly include phthalates (such as dibutyl phthalate and dioctyl phthalate); trimellitates (such as trioctyl trimellitate); polyesters (such as polybutylene adipate); phosphate esters (such as tricresyl phosphate); and chlorinated hydrocarbons (such as chlorinated paraffins). Bio-based plasticizers are prepared from renewable biomass (such as vegetable oils, natural resins, and starch). It mainly includes epoxy vegetable oil esters, cashew phenolic esters, castor oil esters, citrate esters, etc.
[0003] Benzene polycarboxylic acids (BPCAs) are a collective term for a class of organic acids, specifically aromatic compounds formed by replacing hydrogen atoms on the benzene ring with carboxyl groups. These range from benzoic acid (one carboxyl group) to benzohexaic acid (six carboxyl groups), including various BPCAs with different carboxyl group isomers. BPCA ester plasticizers derived from BPCAs are organic compounds with a benzene ring as their core skeleton and containing one or more carboxyl ester groups. Based on the number of carboxyl groups substituted on the benzene ring, they can be classified into monocarboxylic acid esters (such as benzoates), dicarboxylic acid esters (such as phthalates, terephthalates, and isophthalates), tricarboxylic acid esters (such as trimellitate), and tetracarboxylic acid esters (such as pyromellitic ester). The main synthetic routes for BPCA plasticizers include direct esterification, transesterification, catalytic conversion, and novel synthetic methods. Direct esterification involves the esterification of phenylcarboxylic acid (or its anhydride) with a fatty alcohol under the action of a catalyst, producing phenylcarboxylic acid ester plasticizers and water. The reaction equation can be represented as: Ar-(COOH)n + n ROH → Ar-(COOR)n + n H2O (where Ar is a benzene ring, n=1, 2, 3, 4; R is an alkyl group). Transesterification is another important synthetic route for phenylcarboxylic acid plasticizers. Its reaction principle involves the transesterification of lower phenylcarboxylic acid esters (such as dimethyl phenylcarboxylate, diethyl phenylcarboxylate, etc.) with higher fatty alcohols under the action of a catalyst, producing the target higher phenylcarboxylic acid ester and a lower alcohol (such as methanol, ethanol, etc.). The reaction equation can be represented as: Ar-(COOR1)n + nR2OH → Ar-(COOR2)n + n R1OH (where R1 is a lower alkyl group, R2 is a higher alkyl group).
[0004] The composition and chemical reactivity of lignite give it the potential to be converted into chemicals through depolymerization. However, the depolymerization products of lignite are extremely complex mixtures with low concentrations of each component, posing significant difficulties and challenges to the separation and utilization of these chemicals. It is well known in the art that the performance of mixtures typically falls between that of their individual components, rarely exceeding that of the optimal pure component. Therefore, existing technologies generally favor the separation and purification of depolymerization products before reuse. Thus, the separation and utilization process of depolymerization products has become a key bottleneck restricting the development of phenylcarboxylic acid-based chemicals prepared from lignite depolymerization. Existing synthetic routes for phenylcarboxylic acid ester plasticizers mainly rely on petroleum, involving long processes and significant CO2 emissions. Therefore, existing synthetic routes are not suitable for the raw material characteristics of coal-based phenylcarboxylic acid ester plasticizers, necessitating the development of alternative synthetic routes. This invention proposes a "low-rank coal route" for plasticizer synthesis, using phenylcarboxylic acid obtained from the oxidative depolymerization of low-rank coals such as lignite as a raw material to prepare phenylcarboxylic acid ester plasticizers. This route is expected to reduce the dependence on petroleum in plasticizer synthesis and enable the non-energy utilization of low-rank coals such as lignite, representing an alternative route for the synthesis of phenylcarboxylic acid ester plasticizers.
[0005] The prior art solutions most similar to this invention mainly fall into the following categories: (1) CN1769260A discloses a method for preparing trimellitic acid tris(C8-10 alcohol) ester, using trimellitic anhydride and C8-10 alcohol as raw materials, and a solid superacid (such as SO42-) as the raw material. 2 - / ZrO2、SO4 2 - / TiO2、SO4 2 A novel synthesis process using sulfuric acid-free catalysis and solvent-free water-carrying method is employed, with esterification reactions carried out using tin oxides (Fe3O4) or divalent tin oxides as catalysts.
[0006] (2) Tetra-isooctyl pyromellitic acid (TOPM) was synthesized from pyromellitic dianhydride and isooctyl alcohol under microwave irradiation and catalysis by tetrabutyl titanate. 2 Simultaneously, solid superacid SO4 was prepared. 2 - / TiO2-SiO2 was used for the synthesis of tributyl citrate (TBC). This study explored the application of microwave-assisted synthesis in the preparation of plasticizers.
[0007] (3) CN111924855B discloses a nano HZSM-5 molecular sieve for preparing pyromellitic acid plasticizers and its preparation method. The nano HZSM-5 molecular sieve is prepared by supercritical hydrothermal synthesis. The molecular sieve has abundant acid sites and has significant advantages as a catalyst for esterification reaction.
[0008] (4) CN108976119B discloses a method for preparing plasticizers using mixed acid anhydrides as raw materials. The mixed acid anhydrides are byproducts generated during the production of pyromellitic dianhydride, wherein the content of trimellitic anhydride is 32-34% and the content of pyromellitic dianhydride is 64-66%. This method uses mixed acid anhydrides and isooctanol as raw materials, and carries out an esterification reaction under nitrogen protection in the presence of stannous oxide as a catalyst. After the reaction, the plasticizer product is obtained by sequentially undergoing de-alcoholization, decolorization, and filtration. It should be noted that the mixed acid anhydride contains only two components, trimellitic anhydride and pyromellitic dianhydride, and its composition is relatively simple, unlike the complex mixture of more than ten phenylcarboxylic acids found in lignite depolymerization products.
[0009] A comprehensive analysis of existing technical solutions reveals the following three main technical problems: (1) The problem of limited sources of raw materials The synthesis of existing phenylcarboxylic acid ester plasticizers is highly dependent on petroleum-based aromatic raw materials (such as phthalic anhydride, trimellitic anhydride, and pyromellitic dianhydride). The stability of petroleum supply and price fluctuations significantly impact production costs. Meanwhile, low-rank coals such as lignite constitute a large proportion of coal reserves, but are currently mainly used for combustion power generation, resulting in high carbon emission intensity and low utilization value. If low-rank coal could be converted into phenylcarboxylic acid chemicals, it is expected to broaden the raw material channels for plasticizer production and reduce dependence on a single petroleum route.
[0010] (2) Bottlenecks in separation and purification at the raw material preparation level Low-rank coals such as lignite can be converted into phenylcarboxylic acid chemicals through oxidative depolymerization, which helps to broaden the raw material sources for these chemicals. However, the depolymerization products of lignite are extremely complex mixtures containing more than ten phenylcarboxylic acid components, ranging from benzoic acid to benzohexanic acid, with each component present in low concentrations and exhibiting similar physicochemical properties. Conventional methods such as distillation, recrystallization, and column chromatography for separating and purifying individual phenylcarboxylic acid components suffer from problems such as long process flows, high solvent consumption, low yields, and high costs. Therefore, the efficient separation and utilization of depolymerization products has become a key bottleneck restricting the development of lignite depolymerization for the preparation of phenylcarboxylic acid chemicals—a recognized technical challenge in this field.
[0011] (3) Barriers of mindset at the level of technological cognition It is well known to those skilled in the art that the performance of a mixture is usually between that of its components and is difficult to surpass the performance level of the optimal pure component. Based on this common understanding, existing technologies for processing lignite depolymerization products generally tend to follow a "separate first, then utilize" technical route (such as existing technologies (1)-(4) which all use single components or simple binary mixed acid anhydrides as raw materials), and there are few reports of using complex mixed phenylcarboxylic acids directly for chemical synthesis. This mindset in technical understanding further reinforces the recognition of the necessity of separating and purifying lignite depolymerization products. Summary of the Invention
[0012] The separation and utilization of depolymerization products from low-rank coals such as lignite has become a key bottleneck restricting the development of phenylcarboxylic acid chemicals prepared from lignite depolymerization. Establishing a utilization route of "low-rank coal depolymerization products → environmentally friendly plasticizers" addresses the dual industrial challenges of the single raw material source in existing petroleum-based routes and the significant bottlenecks in separation and application in coal-based routes. This invention aims to establish a synthetic route for coal-based phenylcarboxylic acid plasticizers, directly converting mixed phenylcarboxylic acids into mixed ester products with synergistic plasticizing effects, realizing the non-energy utilization of low-rank coals such as lignite, and providing a "low-rank coal route" for the synthesis of phenylcarboxylic acid ester plasticizers.
[0013] The technical solution adopted in this invention is as follows: In a first aspect, the present invention provides a coal-based phenylcarboxylic acid ester plasticizer, wherein the plasticizer is a mixed ester obtained by esterification reaction of coal-based phenylcarboxylic acid obtained by depolymerization of lignite by ruthenium ion catalytic oxidation with C4-C10 fatty alcohol; wherein the C4-C10 fatty alcohol is one or more of n-butanol, isobutanol, n-octanol or isooctanol.
[0014] Preferably, the C4-C10 fatty alcohol is n-butanol or isooctyl alcohol.
[0015] Preferably, the coal-based phenylcarboxylic acid is a mixture containing multiple phenylcarboxylic acid components, including two or more of phthalic acid, triphenylcarboxylic acid, tetraphenylcarboxylic acid, pentanoic acid, and hexaphenylcarboxylic acid.
[0016] Secondly, the present invention provides a method for preparing a coal-based phenyl carboxylic acid ester plasticizer, comprising the following steps: (1) Lignite was depolymerized by ruthenium ion catalytic oxidation to obtain a depolymerization product containing a mixture of phenylcarboxylic acids; (2) Using the phenylcarboxylic acid mixture obtained in step (1) as raw material, without fine separation, it is directly esterified with C4-C10 fatty alcohol in the presence of a catalyst, and after post-treatment, coal-based phenylcarboxylic acid ester plasticizer is obtained.
[0017] Preferably, the conditions for the ruthenium ion catalytic oxidation depolymerization method in step (1) are as follows: using anhydrous ruthenium trichloride (RuCl3) as a catalyst and sodium periodate (NaIO4) as an oxidant, the reaction is carried out at 30~40 °C for 12~48 h in a mixed solvent of carbon tetrachloride (CCl4), acetonitrile (CH3CN) and water (H2O).
[0018] Preferably, the catalyst in step (2) is p-toluenesulfonic acid or tetrabutyl titanate.
[0019] Preferably, the esterification reaction conditions in step (2) are: reaction temperature of 80~220℃, alcohol-acid molar ratio of 20:1~50:1, and reaction time of 1~24 hours.
[0020] Further preferred, the reaction temperature is 100~200℃, and the reaction time is 2~20 hours.
[0021] More preferably, when the fatty alcohol is n-butanol, the reaction temperature is 150~170℃ and the alcohol-acid molar ratio is 35:1~45:1; when the fatty alcohol is isooctyl alcohol, the reaction temperature is 170~190℃ and the alcohol-acid molar ratio is 25:1~35:1.
[0022] Preferably, the post-treatment in step (2) includes: removing excess fatty alcohol by vacuum distillation, and washing with sodium carbonate solution and saturated saline solution until neutral.
[0023] Thirdly, the present invention provides the application of a coal-based phenylcarboxylate plasticizer or a coal-based phenylcarboxylate plasticizer prepared by the above preparation method in improving the heat resistance, migration resistance and / or flexibility of polyvinyl chloride.
[0024] Preferably, the application involves mixing coal-based phenylcarboxylic acid ester plasticizer with polyvinyl chloride in an organic solvent, followed by casting to obtain a plasticized polyvinyl chloride sample.
[0025] Compared with the related technologies known to the inventors, one of the technical solutions of the present invention has the following beneficial effects: (1) Innovation in raw material sources: Using lignite, which is abundant and inexpensive, as raw material, it replaces petroleum-based aromatic raw materials, thus broadening the raw material sources for plasticizer production.
[0026] (2) Innovative process route: The mixed phenylcarboxylic acid obtained from lignite depolymerization is directly used for esterification reaction without the need for complicated separation and purification steps, thus breaking through the key bottleneck of lignite depolymerization product utilization.
[0027] (3) Excellent performance and breakthrough of technical bias: This invention directly utilizes complex coal-based mixed phenylcarboxylic acids to successfully prepare a high-performance plasticizer. This challenges and overcomes the conventional technical understanding in the field that "the performance of mixtures is difficult to surpass that of pure components" and "separation must be performed before utilization", providing strong empirical evidence for the feasibility of this technical path. Experiments have shown that this mixed ester plasticizer exhibits good compatibility and plasticizing effect in PVC. Its heat resistance stability (carbon residue at 750 ℃ is higher than that of DBP / DIOP) and migration resistance (mass loss rate in petroleum ether is lower than that of DBP) are particularly outstanding. Its comprehensive performance is comparable to that of commercial petroleum-based plasticizers, and some properties (such as heat resistance stability and migration resistance) are even more superior.
[0028] (4) Environmentally friendly: It realizes the transformation of lignite from "low-value energy" to "chemical raw material", reducing carbon emissions. Attached Figure Description
[0029] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0030] Figure 1 RICO depolymerization process using ruthenium ion catalytic oxidation of lignite.
[0031] Figure 2 Synthetic route for preparing plasticizers by esterification of phenylcarboxylic acid products from lignite depolymerization.
[0032] Figure 3 Preparation process of PVC samples plasticized with coal-based phenylcarboxylic acid plasticizer.
[0033] Figure 4 Factors affecting the synthesis of plasticizers from coal-based benzyl carboxylic acid with n-butanol and isooctyl alcohol: (a) reaction temperature; (b) alcohol-acid molar ratio; (c) reaction time.
[0034] Figure 5 Infrared spectrum of plasticizer synthesized from phenylcarboxylic acid. Note: PA: phthalic acid; DBP: dibutyl phthalate; DIOP: diisooctyl phthalate; L-BBE: butyl phenylcarboxylate.
[0035] Figure 6 Thermogravimetric analysis of different PVC samples: (a) Thermogravimetric curve (TG); (b) Differential thermogravimetric curve (DTG).
[0036] Figure 7 Stress-strain curves of different PVC samples.
[0037] Figure 8 Shore hardness values of different PVC samples.
[0038] Figure 9 Dynamic mechanical analysis (DMA) curves for different PVC samples. Note: The temperature corresponding to the tanδ peak is the measured glass transition temperature (Tg).
[0039] Figure 10 Microscopic fracture morphology of plasticized PVC samples: (a, e) morphology of uPVC (pure polyvinyl chloride without plasticizer) samples at 100 µm and 10 µm; (b, f) morphology of PVC-DBP samples at 100 µm and 10 µm; (c, g) morphology of PVC-DIOP samples at 100 µm and 10 µm; (d, h) morphology of PVC-L-BBE samples at 100 µm and 10 µm.
[0040] Figure 11 Migration of PVC samples in different solvents at 25 °C: (a) deionized water; (b) anhydrous ethanol; (c) petroleum ether.
[0041] Figure 12 Migration of PVC samples in different solvents at 6 °C: (a) deionized water; (b) anhydrous ethanol; (c) cyclohexane.
[0042] Figure 13 The HPLC chromatograms of phenylcarboxylic acid in lignite depolymerization products, and the assignments of R1-R8 are listed in Table 1.
[0043] Figure 14GC-MS analysis results of benzene polycarboxylic acid esters in lignite ruthenium ion-catalyzed oxidative depolymerization products; Peak 1: dimethyl phthalate; Peak 2: trimethyl 1,2,3-benzenetricarboxylate; Peak 3: trimethyl 1,2,4-benzenetricarboxylate; Peak 4: tetramethyl 1,2,4,5-benzenetetracarboxylate; Peak 5: tetramethyl 1,2,3,5-benzenetetracarboxylate; Peak 6: tetramethyl 1,2,3,4-benzenetetracarboxylate; Peak 7: tetramethyl phenylpentacarboxylate; Peak 8: tetramethyl phenylhexacarboxylate.
[0044] Figure 15 Mass spectrum of dimethyl phthalate in EI full scan mode at a retention time of 14.9 min.
[0045] Figure 16 Mass spectrum of trimethyl 1,2,3-benzenetricarboxylate at a retention time of 18.6 min in EI full scan mode.
[0046] Figure 17 Mass spectrum of trimethyl 1,2,4-benzenetricarboxylate at a retention time of 18.7 min in EI full scan mode.
[0047] Figure 18 Mass spectrum of tetramethyl 1,2,4,5-benzenetetracarboxylate at a retention time of 21.1 min in EI full scan mode.
[0048] Figure 19 Mass spectrum of tetramethyl 1,2,3,5-benzenetetracarboxylate at a retention time of 21.3 min in EI full scan mode.
[0049] Figure 20 Mass spectrum of tetramethyl 1,2,3,4-benzenetetracarboxylate at a retention time of 21.7 min in EI full scan mode.
[0050] Figure 21 Mass spectrum of phenylpentacarbate at a retention time of 23.5 min in EI full scan mode.
[0051] Figure 22 Mass spectrum of hexabenzoate in EI full scan mode at a retention time of 25.1 min. Detailed Implementation
[0052] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0053] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.
[0054] Plasticizers are a class of high-boiling-point, low-volatility organic compounds that effectively improve the flexibility, ductility, processability, and low-temperature performance of polymer materials (especially thermoplastics) by intercalating between polymer molecular chains and weakening the inter-chain interaction forces.
[0055] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0056] The preparation and application process of the coal-based phenylcarboxylic acid plasticizer provided by this invention mainly includes three steps: oxidative depolymerization of lignite (… Figure 1 ), esterification reaction of depolymerization products ( Figure 2 ) and the preparation of plasticized PVC samples with plasticizers ( Figure 3 The details are as follows: Example 1: Preparation of a plasticizer from coal-based phenylcarboxylic acid (1) The ruthenium ion-catalyzed depolymerization reaction of lignite was carried out in a 1000 mL round-bottom flask. Commercially available Shengli lignite (5 g), anhydrous ruthenium trichloride (0.05 g), sodium periodate (100 g), and a mixed solvent of carbon tetrachloride, acetonitrile and water in a volume ratio of 2:2:3 (total volume 700 mL) were added sequentially to a 1000 mL round-bottom flask. The mixture was placed in a 35 ℃ water bath and magnetically stirred for 24 h.
[0057] (2) The mixture is filtered through a vacuum filter device equipped with a 0.2 µm organic filter membrane, and the filtrate and filter cake are collected. After separation by a separatory funnel, an aqueous solution containing phenylcarboxylic acids (BPCAs) is obtained, which is the depolymerization supernatant.
[0058] (3) Adjust the pH of the depolymerization supernatant to <1.5, and extract it three times with an equal volume of distilled butanone, each extraction time being 1 h, and collect the extract. Remove the butanone from the collected butanone phase by rotary evaporation under reduced pressure at 65 ℃, and dry the resulting solution in an oven at 65 ℃ for 12 h to remove residual butanone, to obtain the solid depolymerization product.
[0059] (3a) Composition analysis of depolymerization product phenylcarboxylic acid The solid depolymerization product obtained in step (3) was dissolved in deionized water to prepare a solution, which was then analyzed by high performance liquid chromatography (HPLC). Chromatographic conditions: Benzyl carboxylic acid was quantitatively analyzed using a high performance liquid chromatograph (HPLC, Shimadzu LC-20AT, Japan). The detector was a 235 nm UV detector, the column was a silica-bonded C18 column (Shimadzu Shim-pack GIST, 5 μm C18, 4.6 mm × 250 mm), mobile phase A was 0.1% phosphoric acid solution, mobile phase B was acetonitrile, the injection flow rate was 0.8 mL / min, the column temperature was 45 ℃, and the binary gradient elution program was as follows: initially, the volume ratio of acetonitrile to 0.1% phosphoric acid aqueous solution was 5:95, which linearly increased to 20:80 within 10 min, held for 35 min, and finally decreased to 5:95 within 2 min, consistent with the initial volume ratio of the two mobile phases.
[0060] Qualitative and quantitative analysis was performed using benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, pyromellitic acid, benzopentaic acid, and benzohexaic acid as standards.
[0061] Figure 13 This is the HPLC chromatogram of phenylcarboxylic acids in the lignite depolymerization products. It can be seen that eight phenylcarboxylic acids were mainly detected in the actual lignite depolymerization products. Peaks R1, R2, R3, R4, R5, R6, R7, and R8 correspond to benzohexaic acid, benzopentaic acid, 1,2,4,5-benzenetetracarboxylic acid, 1,2,3,4-benzenetetracarboxylic acid, 1,2,3,5-benzenetetracarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,3-benzenetricarboxylic acid, and phthalic acid, respectively.
[0062] Table 1 lists the specific concentrations of each component in the depolymerization solution. The results show that the total content of benzotricarboxylic acid and benzotetracarboxylic acid is the highest in the depolymerization products, while benzopentaic acid, benzohexaic acid and phthalic acid are also present.
[0063] Table 1. Composition and content of phenylcarboxylic acid in lignite depolymerization products
[0064] To further confirm the structure of phenylcarboxylic acid in the depolymerization product, the solid depolymerization product was esterified and derivatized (esterified with methanol to generate the corresponding methyl phenylcarboxylic acid) and then analyzed by GC-MS. The results are as follows: Figure 14-22 As shown.
[0065] Figure 14This is a GC-MS total ion chromatogram of benzene polycarboxylic acid esters in the ruthenium ion-catalyzed oxidative depolymerization products of lignite. Peaks 1-8 in the figure correspond to: dimethyl phthalate (peak 1), trimethyl 1,2,3-benzenetricarboxylate (peak 2), trimethyl 1,2,4-benzenetricarboxylate (peak 3), tetramethyl 1,2,4,5-benzenetetramethylate (peak 4), tetramethyl 1,2,3,5-benzenetetramethylate (peak 5), tetramethyl 1,2,3,4-benzenetetramethylate (peak 6), tetramethyl phenylpentacarboxylate (peak 7), and tetramethyl phenylhexacarboxylate (peak 8), respectively.
[0066] Figure 15-22 These are the mass spectra corresponding to the components mentioned above. Figure 15 This is the mass spectrum of dimethyl phthalate. Figure 16 This is the mass spectrum of trimethyl 1,2,3-benzenetricarboxylate. Figure 17 This is the mass spectrum of trimethyl 1,2,4-benzenetricarboxylate. Figure 18 This is the mass spectrum of tetramethyl 1,2,4,5-phenyltetracarboxylate. Figure 19 This is the mass spectrum of tetramethyl 1,2,3,5-phenyltetracarboxylate. Figure 20 This is the mass spectrum of tetramethyl 1,2,3,4-phenyltetracarboxylate. Figure 21 This is the mass spectrum of phenylpentacarbonate. Figure 22 This is the mass spectrum of hexamethylbenzene ester. The structures of each component were further confirmed by comparison with a standard mass spectrum library.
[0067] The above results indicate that lignite, after being catalytically oxidized and depolymerized by ruthenium ions, can yield a complex mixture containing various benzoic acids such as phthalic acid, triphenylcarboxylic acid, tetraphenylcarboxylic acid, pentanoic acid, and hexaphenylcarboxylic acid, with triphenylcarboxylic acid and tetraphenylcarboxylic acid being the main components.
[0068] (4) The solid depolymerization product obtained in step (3) (total carboxyl group of 2 mmol) was then added to the catalyst p-toluenesulfonic acid (0.0266 g, 7% of the total carboxyl group molars), and n-butanol was added at an alcohol-acid molar ratio of 40:1. The mixture was then placed in a high-pressure reactor. After sealing the reactor, nitrogen gas was introduced for three purging cycles to completely remove air from the reactor. Subsequently, nitrogen gas was introduced into the reactor to an initial pressure of 2 MPa, and the temperature was raised to 160°C for esterification reaction, with a reaction time of 18 h.
[0069] (5) After the reaction is complete, immediately transfer the reactor to an ice-water bath to cool to room temperature. After the gas inside the reactor is slowly released, weigh 100 µL of the reaction solution into an Erlenmeyer flask and perform quantitative analysis according to the national standard GB / T 1668-2008 to determine the acid value of the reaction solution to calculate the esterification rate. The remaining reaction solution is subjected to vacuum distillation to remove excess alcohol, and then repeatedly washed with 5 wt.% sodium carbonate solution and saturated saline solution until neutral to obtain a pure ester, which is coal-based phenylcarboxylic acid butyl ester (hereinafter referred to as L-BBE).
[0070] Infrared spectroscopy characterization To confirm the chemical structure of the coal-based phenylcarboxylate butyl ester prepared in this invention, infrared spectroscopy was performed on the raw material phthalic acid (PA, as a comparison), the commercial plasticizers dibutyl phthalate (DBP) and diisooctyl phthalate (DIOP, as a control), and the coal-based phenylcarboxylate butyl ester (L-BBE) prepared in Example 1. The results are as follows: Figure 5 As shown.
[0071] from Figure 5 Phthalic acid can be observed at 3400-3650 cm⁻¹. -1 The -OH stretching vibration peak is observed at 3000-2850 cm⁻¹. -1 Only a weak aromatic CH absorption peak is present at this location, consistent with the structural characteristics of aromatic carboxylic acids. Meanwhile, at 1680 cm⁻¹... -1 A strong absorption peak appears at 1720 cm⁻¹, corresponding to the C=O stretching vibration of carboxylic acid. Due to the strong hydrogen bonding between carboxylic acid molecules, the wavenumber of this carbonyl characteristic peak is significantly lower than that of the carbonyl absorption position in ester compounds. After esterification, the hydroxyl signal peak disappears, and the peak value is 1720 cm⁻¹. -1 The presence of a C=O stretching vibration peak at the ester group further confirms the existence of the ester group structure.
[0072] Example 2 Preparation of coal-based isooctyl phenylcarboxylate (L-OBE) This embodiment is basically the same as Example 1, except that the fatty alcohol used in the esterification reaction and the reaction conditions are different.
[0073] The specific steps are as follows: (1)~(3) are the same as steps (1)~(3) in Example 1, to obtain solid phenylcarboxylic acid, the lignite depolymerization product, and to determine its carboxyl content.
[0074] (4) Based on the carboxyl content determined in step (3), weigh out 2 mmol of solid depolymerization product equivalent to the total carboxyl content, add p-toluenesulfonic acid as a catalyst (7 mol% of the total carboxyl content), and add isooctanol at an alcohol-acid molar ratio of 30:1. Place the mixture into a high-pressure reactor. After sealing the reactor, purge it with nitrogen three times to completely remove air from the reactor. Then, purge the reactor with nitrogen until the initial pressure is 2 MPa, and heat it to 180°C for esterification reaction. The reaction time is 18 h.
[0075] (5) After the reaction is completed, the reaction vessel is immediately moved into an ice-water bath to cool to room temperature. After the gas inside the vessel is slowly released, the reaction solution is subjected to vacuum distillation to remove excess isooctyl alcohol. Then, it is washed repeatedly with 5wt.% sodium carbonate solution and saturated salt water solution until neutral to obtain pure ester, which is coal-based phenylcarboxylic acid isooctyl ester (hereinafter referred to as L-OBE).
[0076] Example 3 Preparation of plasticized PVC samples Plasticized PVC samples were prepared using a solution casting method. 40 g of PVC powder, 16 g of plasticizer (using L-BBE prepared in Example 1, L-OBE prepared in Example 2, and commercial plasticizers DBP and DIOP as controls), and 500 mL of tetrahydrofuran (THF) were added to a beaker, sealed with plastic wrap, and magnetically stirred for 24 h until transparent. The mixture was transferred to a glass evaporator, sealed with plastic wrap, and small, uniformly dense holes were punched in the plastic wrap. After complete solvent evaporation, plasticized PVC samples were obtained. Samples prepared using butyl phthalate, isooctyl phthalate, dibutyl phthalate, and diisooctyl phthalate were designated PVC-L-BBE, PVC-L-OBE, PVC-DBP, and PVC-DIOP, respectively.
[0077] Optimization experiment of esterification reaction conditions Using the unseparated lignite depolymerized mixed phenylcarboxylic acid (hereinafter referred to as "mixed phenylcarboxylic acid") obtained in steps (1) to (3) of Example 1 as raw material, plasticizers were synthesized by esterification reactions with n-butanol and isooctanol, respectively. The effects of reaction temperature, alcohol-acid molar ratio, and reaction time on the esterification rate were systematically investigated using a single-factor method. The esterification rate was determined according to the national standard GB / T 1668-2008, and the acid value of the reaction solution was calculated according to the following formula: Esterification rate (%) = (Initial acid value - Acid value after reaction) / Initial acid value × 100% Each experiment was repeated three times, and the average value was taken. The results are as follows: Figure 4 As shown.
[0078] (a) Effect of reaction temperature With a fixed alcohol-acid molar ratio of 30:1 and a reaction time of 12 h, the effect of reaction temperature on the esterification rate was investigated. The results are as follows: Figure 4As shown in (a), the esterification rates of L-BBE and L-OBE initially increased and then decreased with increasing reaction temperature, indicating a significant difference in their optimal reaction temperatures. At 100 °C, the esterification rates of L-BBE and L-OBE were only 54.3% and 54.6%, respectively. When the temperature rose to 160 °C, the esterification rate of L-BBE reached a peak of 82.5%, while the esterification rate of L-OBE reached its maximum value of 84.4% at 180 °C. After exceeding the optimal reaction temperature, further heating led to a significant decrease in the esterification rate. At 200 °C, the esterification rates of L-BBE and L-OBE decreased to 70.5% and 75.5%, respectively. Comparing the two products, it can be found that the optimal reaction temperature for L-OBE is higher, and within the range of 100–200 °C, the esterification rate of L-OBE is slightly higher than that of L-BBE at the same temperature. This is because isooctyl alcohol has a much higher boiling point (185 °C) than n-butanol (117.7 °C), and can still maintain a stable liquid-phase reaction state at high temperatures. In contrast, n-butanol is easily volatilized at high temperatures, which leads to a rapid decrease in the alcohol concentration in the reaction system. Therefore, the optimal reaction temperature of L-BBE is relatively low, and the decrease in esterification rate is more significant at high temperatures.
[0079] (b) Effect of alcohol-acid molar ratio With the reaction temperature fixed at 160 ℃ (L-BBE) or 180 ℃ (L-OBE) and the reaction time at 12 h, the effect of the alcohol-acid molar ratio on the esterification rate was investigated. The results are as follows: Figure 4 As shown in (b), the esterification rates of both L-BBE and L-OBE initially increased and then decreased with increasing alcohol-acid molar ratio, reaching peak values of 89.2% and 88.0% at alcohol-acid molar ratios of 40:1 and 30:1, respectively. Within the alcohol-acid molar ratio range of 10:1 to 30:1, the esterification rate continuously increased with increasing alcohol content. Once the alcohol-acid molar ratio exceeded its peak, further increases in alcohol content led to a significant decrease in the esterification rates of L-BBE and L-OBE to 78.0% and 71.1%, respectively. This is because excess alcohol significantly dilutes the effective concentrations of phenylcarboxylic acid and catalyst in the reaction system, altering the polar environment of the reaction system, producing a solvation effect, reducing the active sites of the catalyst, and thus inhibiting the forward esterification reaction, ultimately resulting in a decrease in the esterification rate. Comparing the two products, it can be found that the esterification rate of L-BBE is more sensitive to changes in the alcohol-acid molar ratio; the decrease in esterification rate caused by excess alcohol is much greater than that of L-OBE. This is because n-butanol is more polar than isooctanol, and its excessive addition has a more significant impact on the polar environment of the reaction system and the activity of the catalyst, thus having a stronger inhibitory effect on the esterification reaction.
[0080] (c) Effect of reaction time With fixed reaction temperatures of 160 ℃ (L-BBE) or 180 ℃ (L-OBE) and alcohol-acid molar ratios of 40:1 (L-BBE) or 30:1 (L-OBE), the effect of reaction time on esterification rate was investigated, and the results are as follows: Figure 4 As shown in (c), the esterification rates of L-BBE and L-OBE increased with increasing reaction time. After 1 h of reaction, the esterification rates of L-BBE and L-OBE were approximately 45% and 44%, respectively; after 2 h, they reached 61.6% and 60.3%, respectively; and after 12 h, the esterification rates of L-BBE and L-OBE reached 89.2% and 88.0%, respectively. At this point, most of the reactive carboxyl groups in the system had completed esterification, and the reaction gradually approached equilibrium. After 12 h, further extending the reaction time had little effect on increasing the esterification rate. After 18 h of reaction, the esterification rate of L-BBE only increased from 89.2% to 91.3%, and the esterification rate of L-OBE only increased from 88.0% to 89.7%, showing a smaller increase in esterification rate. This is because in the early stage of the reaction, the concentration of reactants in the system is high, and the forward esterification reaction rate is much greater than the reverse reaction rate, so the esterification rate increases rapidly with time. As the reaction proceeds, the concentration of reactants gradually decreases, while the concentration of the product ester and water continuously increases, and the reverse reaction rate continues to accelerate. The forward and reverse reactions gradually tend to a dynamic equilibrium. At this point, continuing to extend the reaction time will not significantly increase the esterification rate, but will instead increase production energy consumption and time costs. At the same time, it may trigger side reactions that lead to a darker color and a decline in quality of the product.
[0081] Summary of optimization results The above optimization results indicate that the optimal reaction conditions for preparing L-BBE using mixed phenylcarboxylic acids as raw materials are: temperature 160℃, alcohol-acid molar ratio 40:1, and reaction time 18 h; the optimal reaction conditions for preparing L-OBE are: temperature 180℃, alcohol-acid molar ratio 30:1, and reaction time 18 h. Examples 1 and 2 adopted these optimal conditions. It should be noted that although the present invention preferably uses the above optimal conditions, esterification reactions can proceed smoothly and yield products with plasticizing effects within a wider range of reaction conditions (e.g., temperature 80~220℃, alcohol-acid molar ratio 20:1~50:1, and reaction time 1~24 h). Those skilled in the art can flexibly adjust the process parameters within the above range according to actual production needs.
[0082] Performance evaluation of the plasticizer prepared in Example 1 in polyvinyl chloride (PVC) (a) Heat resistance stability Thermogravimetric analysis was used to characterize the thermal degradation behavior of pure PVC (uPVC), PVC-DBP, PVC-DIOP, and PVC-L-BBE samples. The results are as follows: Figure 6As shown in the figure. The results indicate that different PVC samples mainly undergo two weight loss stages. The first major weight loss stage (200~350 ℃) is the most significant thermal weight loss range for PVC, corresponding to the process of removing hydrogen chloride (HCl) from the molecular chain, resulting in a rapid decrease in sample mass. uPVC exhibits the fastest weight loss rate, while the weight loss curve of the plasticizer-modified samples is flatter, indicating that the plasticizer can effectively delay the release of HCl and improve the thermal stability of PVC. The second major weight loss stage (350~550 ℃) is mainly due to the breakage of the PVC main chain, aromatization, and the thermal decomposition of the plasticizer itself. Among them, PVC-DBP and PVC-DIOP show significantly higher weight loss amplitudes than uPVC, while the weight loss trend of PVC-L-BBE is more moderate, reflecting the excellent high-temperature thermal stability of coal-based phenylcarboxylic acid plasticizers. High-temperature char rate is an important indicator for evaluating the heat resistance and flame retardant properties of materials. The PVC-L-BBE sample has the highest char rate at 750 ℃, indicating that coal-based phenylcarboxylic acid plasticizers can significantly improve the high-temperature char content of PVC, which is beneficial for improving the thermal stability and flame retardancy of the material.
[0083] (b) Mechanical properties Figure 7 The stress-strain curves for PVC samples with different plasticizers, and detailed data from mechanical property tests are listed in Table 2. Figure 7 The tensile stress-strain curves show that, compared to uPVC (3.82 MPa), all three plasticizers significantly improved the tensile strength of PVC. PVC-DIOP exhibited the highest tensile strength (8.61 MPa). While PVC-L-BBE, as a coal-based phenylcarboxylic acid plasticizer, showed slightly lower tensile strength than samples plasticized with commercial plasticizers DIOP and DBP, it still significantly improved over uPVC, demonstrating good plasticizing performance. The elongation at break of the plasticized PVC samples was also effectively improved. PVC-DIOP showed the best tensile properties with an elongation at break of 614.0%, while PVC-DBP had an elongation at break of 520.0%, indicating that DIOP-plasticized samples had better ductility than DBP. L-BBE had an elongation at break of 360.7%, lower than samples plasticized with commercial plasticizers, but still better than unplasticized samples, indicating a significant improvement in the flexibility of PVC. These results demonstrate that even without separation and purification, the coal-based mixed phenylcarboxylic acid esters of this invention exhibit good plasticizing performance.
[0084] Figure 8The results show the Shore hardness values of pure PVC (uPVC) and three plasticized PVC samples. The results indicate that pure uPVC has the highest hardness, at 54 HD. The Shore hardness of the PVC samples plasticized by the three plasticizers is lower than that of uPVC, with PVC-DBP, PVC-DIOP, and PVC-L-BBE having hardnesses of 22 HD, 29 HD, and 35 HD, respectively. This indicates that all three plasticizers effectively weaken the interactions between PVC molecular chains, reducing the material's rigidity. Compared to DBP and DIOP plasticizers, L-BBE has a relatively weaker plasticizing effect and a slightly higher hardness value. This is mainly attributed to the larger number of benzene rings in the L-BBE molecule, resulting in stronger molecular chain rigidity. This limits its diffusion ability when inserting into the gaps between PVC molecular chains, making it difficult to fully penetrate the inter-chain region. Simultaneously, its larger molecular volume restricts the uniform distribution of the plasticizer in the PVC matrix to some extent, weakening the shielding effect on inter-chain interactions. Therefore, its effect on reducing material rigidity is relatively limited, reflecting the significant influence of differences in plasticizer molecular structure on the plasticizing effect.
[0085] Table 2 Mechanical property data of different PVC samples uPVC 3.82 153.06 2.39 PVC-DBP 6.02 520.03 1.19 PVC-DIOP 8.61 614.02 1.47 PVC-L-BBE 5.74 360.69 1.52 (c) Dynamic mechanical analysis In dynamic mechanical analysis (DMA) testing, the temperature corresponding to the peak tanδ is usually defined as the glass transition temperature (Tg) measured by the DMA method. The plasticizing efficiency of different plasticizers can be evaluated by the range of change of the glass transition temperature (Tg) and its relative rate of change. Figure 9 The DMA test curves for different PVC samples are shown in the figure. As can be seen, all three added plasticizers effectively reduced the glass transition temperature (Tg) of PVC. The uPVC sample had the highest Tg (53.3 ℃), indicating that due to strong dipole-dipole interactions and van der Waals forces between pure PVC molecular chains, chain segment movement needs to overcome a high energy barrier, resulting in a glassy state at room temperature and exhibiting hard and brittle characteristics. After adding plasticizers, the Tg of all samples decreased significantly, indicating that plasticizers can effectively weaken the intermolecular forces of PVC, increase free volume, and activate chain segment movement at lower temperatures, allowing the material to enter the elastic state earlier. Among them, the PVC-DIOP sample had the lowest Tg (21.5 ℃) and the highest plasticizing efficiency. The PVC-DBP sample had the second lowest Tg (30.7 ℃), with a slightly lower plasticizing efficiency than DIOP. The PVC-L-BBE sample had a relatively high Tg (41.4 ℃) and the smallest Tg decrease. This is because the L-BBE molecule contains a large number of benzene ring structures, which make the molecule more rigid and still have a certain restrictive effect on chain segment movement.
[0086] (d) Microscopic morphology analysis Figure 10SEM morphology of fracture surfaces of pure PVC and PVC samples plasticized with different plasticizers. SEM results show that the fracture surfaces of pure PVC samples (…) Figure 10 a) and e) exhibit typical brittle fracture morphology, with a dense fracture surface and nodular structure, which may be attributed to the poor compatibility between PVC chains. After adding plasticizers, such as... Figure 10 (bd) The microscopic fracture morphology of the PVC sample becomes rougher, the number of fracture points increases, and the morphology changes from brittle fracture to ductile fracture, with slight traces of plastic deformation appearing. Figure 10 (fh) shows that the plasticized sample has a smooth and flat cross-sectional morphology, indicating good compatibility between the plasticizer and the PVC matrix. The microstructure shows that the plasticizer molecules are uniformly distributed in the PVC matrix, and no porous structures or obvious aggregates caused by plasticizer migration due to insufficient compatibility were observed, further confirming that the addition of plasticizer can effectively improve the flexibility of PVC molecular chains.
[0087] (e) Migration resistance Figure 11The curves showing the change in mass loss rate of PVC samples plasticized with three plasticizers (PVC-DBP, PVC-DIOP, and PVC-L-BBE) at 25 °C in deionized water, anhydrous ethanol, and petroleum ether as a function of immersion time are presented. The mass loss rate quantitatively characterizes the degree of plasticizer migration from the PVC matrix to the solvent. The mass loss rate of all samples increased with prolonged immersion time, with lower migration rates in deionized water (the most polar environment). The mass loss rate remained low after 120 h (maximum 7.1%), because polar water molecules have poor compatibility with phenylcarboxylic acid ester plasticizers, making it difficult to effectively penetrate the PVC matrix and extract the plasticizer components. In anhydrous ethanol (moderately polar), the sample mass loss rate increased significantly, reaching a maximum of 15.9% after 120 h. This is because the polarity of ethanol is closer to that of plasticizer molecules, which can cause the plasticizer to dissolve by swelling the PVC molecular chains and weakening the interaction between the plasticizer and the PVC matrix. In petroleum ether (non-polar), the highest mass loss rate of the sample was 19.7% after 120 h. Non-polar petroleum ether exhibits the best compatibility with ester plasticizers, rapidly penetrating the PVC matrix and driving small molecules to diffuse into the solvent phase, resulting in the most vigorous migration behavior. Even under this harsh migration environment, the mass loss rate of the PVC-L-BBE sample was still lower than that of PVC-DBP, indicating that its bonding with the PVC matrix is more stable and it exhibits superior migration resistance. Comparing the mass loss rates of the three PVC samples: PVC-DIOP < PVC-L-BBE < PVC-DBP, it can be seen that DIOP plasticizer has the best migration resistance. This is mainly attributed to the larger molecular weight and longer molecular chain of DIOP, resulting in higher diffusion resistance in the PVC matrix and making it difficult to be extracted by the solvent. L-BBE plasticizer is the next best option. Compared to the commercial plasticizer DBP, this plasticizer has more benzene ring structures. Its conjugation effect can enhance the polarity of the ester group in the molecule. At the same time, it generates π-σ and π-dipole interactions with the PVC molecular chain through the π-electron system, which improves the bonding stability between the plasticizer and the matrix, making it more resistant to migration in solvent environments.
[0088] (f) Low-temperature migration resistance PVC samples plasticized with three plasticizers were placed at 6 ℃, and the changes in their mass loss rate with immersion time in deionized water, anhydrous ethanol, and cyclohexane were investigated. The results are as follows: Figure 12As shown in the figure. The results indicate that the mass loss rate of all samples increased with prolonged soaking time, with the lowest mass loss rate in deionized water (maximum 4.4%). In anhydrous ethanol (moderately polar) solvent, the mass loss rate increased significantly, reaching a maximum of 8.7% at 120 h. This is because the polarity of ethanol is closer to that of plasticizer molecules, which can weaken intermolecular interactions by swelling PVC segments, promoting the migration of small molecules. However, the low temperature environment still significantly slowed down the migration rate, and the overall mass loss rate was lower than that of the corresponding samples at 25 °C. In cyclohexane (non-polar) solvent, the highest mass loss rate of the samples at 120 h was approximately 11.3%. Non-polar cyclohexane has the best compatibility with ester plasticizers, can efficiently penetrate the PVC matrix and drive small molecules to diffuse into the solvent phase, and is the medium with the strongest migration driving force among the three solvents. Even at low temperatures, its extraction capacity is still significantly higher than that of polar solvents. Comparing the mass loss rates of the three PVC samples: PVC-DIOP < PVC-L-BBE < PVC-DBP, it can be seen that L-BBE, as a coal-based plasticizer, can form stable intermolecular interactions with the PVC matrix. While exerting a plasticizing effect, it effectively enhances the matrix's ability to bind small molecules and inhibits migration behavior. Compared with the data at 25 ℃, the mass loss rate of all samples is significantly reduced at 6 ℃. This is because the lower temperature weakens the mobility of PVC molecular chain segments and reduces the diffusion coefficient of small molecules, thereby effectively delaying the migration process and demonstrating the significant regulatory effect of temperature on migration behavior.
[0089] Performance Evaluation Summary The performance evaluation of the coal-based plasticizer prepared in Example 1 in polyvinyl chloride (PVC) showed that, compared with pure PVC, the coal-based butyl phenylcarboxylate plasticizer significantly improved the elongation at break of PVC. Although the tensile strength was slightly lower than that of DBP and DIOP, it was still higher than that of pure PVC. It maintained good mechanical strength while improving flexibility, indicating that it has good flexibility and plasticizing effect. Microscopic morphology (SEM) revealed that the plasticizer has good compatibility with the PVC matrix. Thermogravimetric analysis (TG) showed excellent heat resistance and flame retardant properties. Furthermore, dynamic mechanical analysis (DMA) results showed that the addition of this plasticizer significantly reduced the glass transition temperature of PVC, further confirming its good plasticizing effect. Migration resistance tests showed that L-BBE had better migration resistance than the commercial plasticizer DBP, maintaining good migration resistance even at low temperatures. Its plasticizing mechanism lies in the insertion of the benzene ring structure in the plasticizer molecule into the interchain gaps of PVC molecules, widening the interchain spacing and weakening the interchain forces; the ester group forms hydrogen bonds with the hydrogen atoms on the PVC molecular chain, reducing the energy barrier for chain segment movement. In addition, this plasticizer exhibits excellent anti-migration ability and heat stability, and has good prospects for industrial application.
[0090] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A coal-based phenyl carboxylic acid ester plasticizer, characterized in that, The plasticizer is a mixed ester obtained by esterification of coal-based phenylcarboxylic acid, obtained by depolymerization of lignite via ruthenium ion catalytic oxidation, and C4-C10 fatty alcohols. The conditions for the ruthenium ion catalytic oxidation depolymerization are: using anhydrous ruthenium trichloride as a catalyst and sodium periodate as an oxidant, reacting at 30-40°C for 12-48 h in a mixed solvent of carbon tetrachloride, acetonitrile, and water; the catalyst is p-toluenesulfonic acid or tetrabutyl titanate. The esterification reaction conditions are: reaction temperature of 80~220 ℃, alcohol-acid molar ratio of 20:1~50:1, and reaction time of 1~24 hours; The C4-C10 fatty alcohol is n-butanol or isooctyl alcohol; The coal-based phenylcarboxylic acid is a mixture containing multiple phenylcarboxylic acid components, including phthalic acid, triphenylcarboxylic acid, tetraphenylcarboxylic acid, pentanoic acid, and hexaphenylcarboxylic acid.
2. A method for preparing the coal-based phenylcarboxylic acid ester plasticizer as described in claim 1, characterized in that, Includes the following steps: (1) Lignite was depolymerized by ruthenium ion catalytic oxidation to obtain a depolymerization product containing a mixture of phenylcarboxylic acids; The conditions for the depolymerization by the ruthenium ion catalytic oxidation method are as follows: using anhydrous ruthenium trichloride as a catalyst and sodium periodate as an oxidant, the reaction is carried out at 30-40°C for 12-48 h in a mixed solvent of carbon tetrachloride, acetonitrile and water. (2) Using the phenylcarboxylic acid mixture obtained in step (1) as raw material, without fine separation, it is directly esterified with C4-C10 fatty alcohol in the presence of a catalyst, and after post-treatment, coal-based phenylcarboxylic acid ester plasticizer is obtained. The catalyst is p-toluenesulfonic acid or tetrabutyl titanate; The esterification reaction conditions are: reaction temperature of 80~220 ℃, alcohol-acid molar ratio of 20:1~50:1, and reaction time of 1~24 hours; The post-treatment includes: removing excess fatty alcohol by vacuum distillation, and washing successively with sodium carbonate solution and saturated brine until neutral.
3. The preparation method according to claim 2, characterized in that, The reaction temperature is 100~200 ℃, and the reaction time is 2~20 hours.
4. The application of a coal-based phenylcarboxylate plasticizer as described in claim 1 or a coal-based phenylcarboxylate plasticizer prepared by the preparation method described in claim 2 or 3 in improving the heat resistance, migration resistance and / or flexibility of polyvinyl chloride.
Citation Information
Patent Citations
Preparation methods and applications of plasticizers prepared from mixed acid anhydrides
CN108976119B
A nano-HZSM-5 molecular sieve for preparing pyromellitic acid plasticizers, its preparation method and application
CN111924855B
Trimellitic tri(C8-9 ol)ester preparation method
CN1769260A
Improvements in or relating to the production of benzene carboxylic acids and estersthereof
GB705862A